RETENSI MODAL PENGETAHUAN DAN SUMBERDAYA INTERNAL PERUSAHAAN - Agustian Budi Prasetya (Jurnal Akuntansi dan Pajak, 2017)
The paper discuss about retention model of  corporate  knowledge capital  and identification internal resources that affect the efectivity of retention of corporate knowledge capital. The research utilize desk research methodes, based on academic literaturs. The paper describe analytically the DeLong and Arif et.all  of knowedge retention model, apply with  retention cases. The paper found that along  with  effort to keep the corporate capital knowledge, company might face threat of loosing the knowledge, the capacity to make decision effectively due to the  mismanagement  of  company internal resurces, such as: staffing, turnover, recruitment, eangement to type of short term project; weak leadership and  prioritizing; ineffective of information technology management. Key words : knowledge retention,  corporate knowledge capital, company internal resources, loss of knowledge